Effect of ultrasonic shot peening on microstructure and properties of 301SS. Issue 16 (10th December 2017) - Li, Kejian; Spartacus, Gabriel; Dong, Jiling; Cao, Pengjun; Shin, Keesam
ABSTRACT: Ultrasonic shot peening (USP) is an efficient way to improve the mechanical behavior of 301 stainless steel by inducing severe plastic deformation on its surface. However, this surface treatment induces complex microstructural evolutions, such as grain refinement and phase transformation. Therefore, a better understanding of those evolution mechanisms is critical to optimize the USP treatment. In this work, we rely on various electron microscope observations to compare a specimen before and after a 5-min shot peening treatment. We found an affected layer of ~450 µm with a significant increase in hardness on the top surface by a factor of 2.7 times. Inside this layer, we noticed a nanoscale grain layer of ~130 µm, the most strengthened layer, containing nanoscale grain of α′, with few γ and a large amount of low angle grain boundaries on the topmost. Afterward, we observed coarse grains with deformation twins, which seem to be a preferential site for martensite nucleation, especially at their intersection, and a high density of dislocation. We also conducted experiments to determine a possible scenario for the microstructural evolution, based on those observations.